Independent medical evaluation for sick-listed patients: a focus group study of GPs´ expectations and experiences - Aase Aamland; Elisabeth Husabo; Silje Maeland (BMC, 2018)
Abstract Background Norwegian general practitioners (GPs) are important stakeholders because they manage 80% of people on long-term sick-leave. Independent medical evaluation (IME) for long-term sick-listed patients is being evaluated in a large randomized controlled trial in one county in Norway in an effort to lower the national sick-leave rate (the NIME trial: Effect Evaluation of IME in Norway). The aim of the current study was to explore GPs' expectations of and experiences with IMEs. Methods We conducted three focus group interviews with a convenience sample of 14 GPs who had had 2-9 (mean 5) of their long-term sick-listed patients summoned to an IME. We asked them to recollect and describe their concrete expectations of and experiences with patients assigned to an IME. Systematic text condensation, a method for thematic cross-case analysis, was applied for analysis. Results To care for and to reassure their assigned sick-listed patients, the participants had spent time and applied different strategies before their patients had attended an IME. The participants welcomed a second opinion from an experienced GP colleague as a way of obtaining constructive advice for further sick-leave measures and/or medical advice. However, they mainly described the IME reports in negative terms, as these were either too categorical or provided unusable advice for further follow-up of their sick-listed patients. The participants did not agree with the proposed routine use of IMEs but instead suggested that GPs should be able to select particularly challenging sick-listed patients for an IME, which should be performed by a peer. Conclusion Our participants showed positive attitudes towards second opinions but found the regular IMEs to be unsuitable. The participants did however welcome IMEs if they themselves could select particularly challenging patients for a mandatory second opinion by a peer but emphasized that IME-doctors should not be able to overrule a GP's sick-leave recommendation. These findings, together with other evaluations, will serve as a basis for the Norwegian government's decision on whether or not to implement IMEs for long-term sick-listed patients. Trial registration ClinicalTrials.gov NCT02524392. Registered 23 June, 2015.